ANALISIS HUBUNGAN LITERASI EKONOMI DENGAN IMPULSIVE BUYING PADA PESERTA DIDIK - Rita Afriany; Bambang Genjik; Okianna Okianna (Universitas Tanjungpura, 2022)
This study aims to describe economic literacy, particularly related to impulsive buying, in SMK Negeri 3 Pontianak students. This study used ten informants, of which 5 were women, and 5 were men from class XI Marketing. Data collection methods in this study were observation, interviews, and documentation. The data analysis used was qualitative. To test the validity of the data using internal validity, transferability, dependability, and confirmability. The results of the research were as follows: (a) from the researcher's point of view, teachers in SMK have given lessons to students about economic literacy and impulsive buying, but in their simple language, resulting in a lack of knowledge about financial literacy and impulsive buying, (b) knowledge about financial literacy among students in SMK is still low, (c) the knowledge related to impulsive buying in students is deficient, and (d) the researcher explained that understanding economic literacy on impulsive buying has a tremendous impact on students; after knowing the explanation from researchers about financial literacy and impulsive buying, students begin to understand that if they know economic literacy, then they will not do impulsive buying.